Radical conservatism and the Heideggerian right: Heidegger, de Benoist, Dugin - Backman, Jussi (Frontiers in Political Science, 2022)
The paper studies the significance of Martin Heidegger's philosophy of history for two key thinkers of contemporary radical conservatism and the Identitarian movement, Alain de Benoist and Aleksandr Dugin. Heidegger's often-overlooked affinities with the German “conservative revolution” of the Weimar period have in recent years been emphasized by an emerging radical-conservative “right-Heideggerian” orientation. I first discuss the later Heidegger's “being-historical” narrative of the culmination and end of the metaphysical foundations of Western modernity in the contemporary Nietzschean era of nihilism and of an emerging postmodern “other beginning” of Western thinking, focused on historical and cultural relativism and particularism. In Heidegger's work of the 1930s and 1940s, we find attempts to apply this historical narrative to interpreting contemporary geopolitical and ideological phenomena in ways that connect Heidegger to certain central ideas and concerns of the conservative revolutionaries, especially Carl Schmitt's geopolitical particularism. De Benoist, the key name of the French Nouvelle Droite and a founding figure of contemporary Identitarianism, is particularly inspired by Heidegger's reading of Nietzsche as the culmination of the “metaphysics of subjectivity” dominating Western modernity. For de Benoist, this modern metaphysics is the root of the “ideology of the Same” underlying the liberal universalism and individualism that he opposes in the name of a cultural ethnopluralism. De Benoist's Russian disciple Dugin bases the pluralistic geopolitics of his radical-conservative “fourth political theory” on the legacy of the conservative revolution, the key intellectual model of which Dugin discovers in Heidegger's notion of the “other beginning”.